FRUSTRATED CHARACTER IN CHOPIN’S THE AWAKENING: A PSYCHOLOGICAL APPROACH - Siggih Daru Kuncara (Kantor Bahasa Kalimantan Timur, 2016)
This paper studied the famous work of Kate Chopin, The Awakening. The core of the study was the main character, Edna Pontellier. The physiological approach was applied in this paper. It used psychological theory of frustration. The theory consisted of the definition and sources of frustation and reactions to frustration. The analysis focused on the frustration happened on the main character, Edna. It explained the process of frustration represented on a sketch. It illustrated the steps how Edna became a frustrated person. From the analysis, it could be seen that Edna at the beginning of the story was an ordinary mother who took care of her family. Then, she changed herself after summer vacation with new ambitions. Her ambitions could be divided into three parts, such as getting independence in life, sex, and love. Later, she failed in gaining her ambitions. This failure led her to frustration. She belonged to a frustrated person due to her reaction in facing problems to reach her independence.